2011
DOI: 10.1590/s0034-737x2011000500015
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade pós-colheita da alface hidropônica em ambiente protegido sob malhas termorefletoras e negra

Abstract: Postharvest quality of hydroponic lettuce in greenhouse shaded with thermo-reflective and black screensQuality characteristics of leafy vegetables are affected by the duration of exposure, quality and intensity of light. This study was carried out under greenhouse conditions to evaluate the postharvest quality of hydroponic lettuce affect by thermo-reflective screens with different percentages of attenuation of solar radiation. The experiment was arranged in a 2 x 5 factorial randomized block design, with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
1
3
1
10
Order By: Relevance
“…For Loose-leaf group (Table 2), when the cultivation was carried out in summer, no statistical differences were found among cultivars, but in autumn and spring, Regiane presented higher performances than Elisa, and in winter, Elisa was the cultivar that stood out. Titratable acidity values shown in Table 2 were higher than those found by Morais et al (2011) and Santos et al (2010), who evaluated cultivars of Green-leaf group in Mossoró, Rio Grande do Norte state and in Botucatu, São Paulo state, respectively, in different farming systems, and found that titratable acidity varies according to the cultivar and the cultivation environment.…”
Section: Resultscontrasting
confidence: 54%
“…For Loose-leaf group (Table 2), when the cultivation was carried out in summer, no statistical differences were found among cultivars, but in autumn and spring, Regiane presented higher performances than Elisa, and in winter, Elisa was the cultivar that stood out. Titratable acidity values shown in Table 2 were higher than those found by Morais et al (2011) and Santos et al (2010), who evaluated cultivars of Green-leaf group in Mossoró, Rio Grande do Norte state and in Botucatu, São Paulo state, respectively, in different farming systems, and found that titratable acidity varies according to the cultivar and the cultivation environment.…”
Section: Resultscontrasting
confidence: 54%
“…In relation to the vitamin C content, the Tabela Brasileira de Composição dos Alimentos (2011) informs that 100 g of fresh curly lettuce has 15.5 mg of vitamin C. Kim et al (2016), reported 2.9 mg.g-1 of vitamin C in crisphead lettuce (Lactuca sativa L.), while for baby Romaine they obtained values between 21 and 40 mg.g-1. Morais et al (2011) observed a vitamin C content of 27.24 mg.100g-1 in lettuce on the day of harvest (similar to the values obtained for treatments 1, 3, 5, 6, 7 and 8). Table 2 shows that during the 14 days of refrigerated storage, for all treatments, a mass reduction (p < 0.05) occurred in the lettuce samples, and from day 5 the decrease in this parameter is higher for all treatments.…”
Section: Resultssupporting
confidence: 85%
“…In this sense, shade screens have been used alone or in combination in protected environments, making the resulting microclimatic conditions appropriate for crop growth. Thus, the harmful effects of high incidence of solar radiation are reduced, also protecting against extreme temperatures (Morais et al, 2011).…”
Section: Introductionmentioning
confidence: 99%